Human brain organoids: an innovative model for neurological disorder research and therapy - Li, Hancheng; Zhu, Junxiao; Li, Jieyu; Wu, Yangkai; Luo, Chaohua; Huang, Yuting; Wu, Jieru; Liu, Wenhua; Wang, Hongwu; Mo, Zhixian (Frontiers in Cellular Neuroscience, 2025)
The emergence of human brain organoids (hBOs) has transformed how we study brain development, disease mechanisms, and therapy discovery. These 3D in vitro neural models closely mimic the cellular diversity, spatial structure, and functional connectivity of the human brain, providing a groundbreaking platform that outperforms traditional 2D cultures and animal models in studying neurodevelopment and neurological disorders. To further explore the potential of hBOs technology, we review current literature focusing particularly on its applications for diagnosing and treating major neurological diseases such as Alzheimer’s disease, Parkinson’s disease, and other related neurological disorders. Using patient-derived induced pluripotent stem cells combined with cutting-edge gene-editing technologies, hBOs enable highly precise mechanistic studies and scalable drug screening. Moreover, we further discuss the advantages and current limitations of hBOs. Despite these challenges, hBOs remain a transformative platform for the development of targeted neurotherapeutics. Collectively, this review offers a solid foundation for advancing neuroscience research and fostering innovative treatment strategies for neurological disorders.